Pengembangan Sistem Informasi Manajemen Produksi Berorientasi Layanan Menggunakan Pendekatan SOA - Sudirman, Bagus; Siswanto , Eko; Nugroho, Didik Setio (LPPM UNIKA Santo Thomas Medan, 2024)
Green Mukti is a youth group founded by the Jatilor village government, Godong District, Grobogan Regency, with the aim of increasing the participation of the younger generation in the agricultural sector, especially in rice production, from planting to processing. However, over time, several problems have emerged, such as inconsistencies in the quality of production results or loss of rice raw materials due to errors in recording during harvest. Therefore, more effective monitoring is needed to ensure that the rice production process runs smoothly. One solution that can be applied is the development of a website with a Service Oriented Architecture (SOA) approach. SOA is an architectural style that offers benefits such as flexibility, reuse in various projects, and integration with various applications. With this service-based website, all stages of production can be monitored and controlled, thereby reducing errors, maintaining quality, and ensuring the availability of rice.